Highly efficient copper-manganese oxide catalysts with abundant surface vacancies for low-temperature water-gas shift reaction. (18th March 2020) - Lang, Yun; Du, Chun; Tang, Yuanting; Chen, Yongjie; Zhao, Yunkun; Chen, Rong; Liu, Xiao; Shan, Bin
Abstract: Efficient and low-cost water-gas shift (WGS) catalysts have aroused much attention for the purification of H2 -rich syngas in the application of fuel cell. In this study, combustion of ethylene glycol and methanol (EGM), fractional precipitation (FP) and template growth (TG) methods have been utilized to synthesize copper-manganese oxide (CMO) catalysts. The prepared CMO catalysts are consisted of spinel Cu1.5 Mn1.5 O4 and Mn2 O3 phases and exhibit porous, polyhedral nanoparticle and nanorod morphologies for EGM, FP and TG, respectively. The low-temperature WGS reaction activities of prepared catalysts follow the sequence: CMO-EGM > CMO-FP > CMO-TG, which are higher than that of CMO catalyst prepared by traditional co-precipitation method. Among them, CMO-EGM catalyst exhibits the highest reaction rate of 122.72 μmolCO g cat. − 1 s −1 at 200 °C, which is much higher than that of commercial Cu/ZnO/Al2 O3 (73.62 μmolCO g cat. − 1 s −1 ). CO-TPSR and DRIFTS analysis reveal the superior activity of CMO-EGM is attributed to the larger amounts of active hydroxyl groups on the surface of catalysts, which correlate well with the high reducibility and abundant surface oxygen vacancies of CMO-EGM catalyst. Graphical abstract: Image 1 Highlights: The CMO catalysts prepared by EGM, FP and TG methods exhibit various morphologies. CMO catalyst prepared by EGM method shows much higher activity than commercial Cu/ZnO/Al2 O3 catalyst. High reducibility and abundant oxygen vacancies contribute to generation of OH groups. The enhanced low-temperature activity is ascribed to more surface active OH groups.